2017
DOI: 10.3389/fpls.2017.00771
|View full text |Cite
|
Sign up to set email alerts
|

Reference Gene Selection for qRT-PCR Normalization Analysis in kenaf (Hibiscus cannabinus L.) under Abiotic Stress and Hormonal Stimuli

Abstract: Kenaf (Hibiscus cannabinus L.), an environmental friendly and economic fiber crop, has a certain tolerance to abiotic stresses. Identification of reliable reference genes for transcript normalization of stress responsive genes expression by quantitative real-time PCR (qRT-PCR) is important for exploring the molecular mechanisms of plants response to abiotic stresses. In this study, nine candidate reference genes were cloned, and their expression stabilities were assessed in 132 abiotic stress and hormonal stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…The RefFinder tool [ 59 ] which compilates four algorithms: geNorm [ 60 ], NormFinder [ 61 ], BestKeeper [ 62 ] and the comparative delta-Ct method [ 63 ] did not evaluate candidate genes congruently with standalone geNorm and NormFinder software. This discrepancy among various analytical tools has been described previously [ 23 , 65 , 66 , 67 , 68 ]. However, despite modest inconsistencies, Sv_ACT and Sv_GAPDH 1 primer pairs were consistently ranked among the first three most stable reference genes, no matter which analytical tool was applied.…”
Section: Discussionmentioning
confidence: 66%
“…The RefFinder tool [ 59 ] which compilates four algorithms: geNorm [ 60 ], NormFinder [ 61 ], BestKeeper [ 62 ] and the comparative delta-Ct method [ 63 ] did not evaluate candidate genes congruently with standalone geNorm and NormFinder software. This discrepancy among various analytical tools has been described previously [ 23 , 65 , 66 , 67 , 68 ]. However, despite modest inconsistencies, Sv_ACT and Sv_GAPDH 1 primer pairs were consistently ranked among the first three most stable reference genes, no matter which analytical tool was applied.…”
Section: Discussionmentioning
confidence: 66%
“…Previous work has also shown that the three programs generate different results under abiotic stress in Vitis vinifera [45]. A comprehensive analysis is therefore necessary to provide ultimate stability rankings for RGs under different treatments, as reported previously [46,47].…”
Section: Discussionmentioning
confidence: 81%
“…However, the accuracy of this method is heavily dependent on data normalization done by stably expressed reference genes. It is now well accepted that a single or a pair of reference genes that are useful for one species or experimental settings may not be equally useful for another species or even for the same species but under different experimental conditions (Morgante et al 2011, De Andrade et al 2017, Niu et al 2017.…”
Section: Discussionmentioning
confidence: 99%